King, Fuller and Dworkin on Natural Law and Hard Cases: An Argument - Muhammad M. Rashid (Selected Topics in Humanities and Social Sciences Vol. 7, 2021)
The issue over natural law vs. positivist law has gotten a lot of attention. Through the use of challenging instances, Ronald Dworkin shows the limitations of positivist law. This argument is enhanced when we combine Martin Luther King Jr.’s interpretation with the voluntarist natural law tradition, as well as Lon Fuller’s "procedural view" and application of the "principles of legality."